Repressed scientists of the philological faculty of Kharkiv University of the first half of the ХХ century - Глибицька, Світлана Борисівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article is written on the basis of the materials collected in the preparation of the publication "The Biobibliographic Dictionary of the Scientists of Kharkov University. T. 3. Phylologists XX – the early of the 21st century. Part 1. Faculty of Philology. Department of Ukrainian Studies of Philosophy Faculty", which is prepared by the Central Scientific Library of the V. N. Karazin Kharkov National University. In the article, based on the biographies of scientists of the first half of the twentieth century, summarized information about repression at the philological faculty of the Kharkov University (and high school formed from it), mainly in the 1920s-1930s and the late 1940s. The names of the repressed scientists are given in the chronology of events and on the departments. The destiny of each scientist (shooting up, exile, dismissal from work) is discribed. The general statistics of repressed philologists is given. Most scholars were repressed in 1933–1934, 1937–1939, after the war persecution was in 1946–1949. Losses at the Faculty of Philology of this time: 20 people were perished (among them 15 shot, 5 died at the expiration), among the other 11 slaves 8 returned alive, in 3 further fate is unknown; 9 were dismissed from work (some of them later recovered); of the 4 people, who worked at the university in the aforementioned years, the further fate is unknown. Let’s list the names of the most famous scientists, who were repressed: Ya. A. Denisov (shot), M. M. Durnovo (shot), G. A. Il’inskij (shot), M. G. Johansen (shot), N. A. Kaganovich (shot), V. D. Koryak (shot), G. O. Kostyuk (exiled), O. M. Leites (dismissed from work), L. Ya. Livshits (exiled), M. F. Nakonechniy (dismissed from work), K. T. Nimchinov (shot), A. S. Paniv (shot), M. Yu. Panchenko (shot), M. A. Plevako (killed in exile), V. L. Polischuk (shot), P. G. Ritter (died in the prison hospital), O. N. Sinyavsky (shot) et al.